Intervensi Keperawatan “Ekofol” pada Pasien Post PCI dalam Meningkatkan Kepatuhan Pengobatan - Pebrianti, Sandra; Shalahuddin, Iwan; Eriyani, Theresia; Nugraha, Bambang Aditya (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Percutaneous coronary intervention (PCI) is the most common therapy for treating CAD through improved myocardial perfusion. The transition from hospital to home is a challenge for CAD patients undergoing PCI. After a brief stay in the hospital, patients have to take a lot of medicine every day, and adjust their lifestyle at home. The purpose of conducting this Evidence Based Practice is to determine the types of nursing interventions that can improve the level of treatment adherence in post PCI patients. The research method used in this review literature is a narrative review type with the title "Nursing Intervention "EKOFOL" in Post PCI Patients. Based on the seven articles analyzed, there are seven different interventions to improve treatment adherence of post-PCI patients. The first article uses education and counseling methods, the other six articles use the same method, namely education, counseling and follow up. The following are the interventions discussed from the seven articles analyzed. Based on the results of the study, it was concluded that there was treatment adherence in post-PCI patients with educational, counseling and follow-up interventions with duration and frequency adjusted back to patient needs. But in one article that has been analyzed, patient treatment adherence is considered quite low despite the intervention. Keywords: Nursing Interventions, Post PCI Patients, Treatment Adherence  ABSTRAK Percutaneous Coronary Intervention (PCI) adalah terapi yang paling umum untuk mengobati CAD melalui peningkatan perfusi miokard. Transisi dari rumah sakit ke rumah merupakan tantangan tersendiri bagi pasien CAD yang menjalani PCI. Setelah dirawat sebentar di rumah sakit, pasien harus meminum banyak obat setiap hari, dan menyesuaikan gaya hidup mereka di rumah. Tujuan melakukan Evidence Based Practice ini adalah untuk mengetahui jenis-jenis intervensi keperawatan yang dapat meningkatkan tingkat kepatuhan pengobatan pada pasien post PCI. Metode penelitian yang digunakan dalam literatur review ini berjenis narrative review dengan judul “Intervensi Keperawatan “EKOFOL” Pada Pasien Post PCI. Berdasarkan tujuh artikel yang dianalisis, terdapat tujuh intervensi yang berbeda untuk meningkatkan kepatuhan pengobatan pasien post PCI. Artikel pertama menggunakan metode edukasi dan konseling, keenam artikel lainnya metode yang sama yaitu edukasi, konseling dan follow up. Berikut merupakan intervensi yang dibahas dari ketujuh artikel yang dianalisis.  Berdasarkan hasil penelitian maka disimpulkan adanya kepatuhan pengobatan pada pasien post PCI dengan intervensi edukasi, konseling dan follow up dengan durasi dan frekuensi yang disesuaikan kembali pada kebutuhan pasien. Namun dalam satu artikel yang telah dianalisis, kepatuhan pengobatan pasien dianggap cukup rendah meskipun telah dilakukan intervensi Kata Kunci: Intervensi Keperawatan, Pasien Post PCI, Kepatuhan Pengobatan